Development and implementation of a self-directed learning readiness scale for undergraduate health professional students - Puja Dulloo; Suman Singh; Neeraj Vedi; Praveen Singh (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: To motivate students toward the path of lifelong learning, it is important to train them for a self-directed learning (SDL) approach, where they identify the need of learning the content as well as look forward to attaining the learning outcome, independently. The level of readiness for SDL will allow the learner to be self-disciplined, self-organized, an effective team builder and communicator, a self-assessor, and a self-reflector, thus being a self-learner with the ability to accept and give constructive feedback. The aim of the study was to develop, validate, and implement the SDL readiness scale for health professional students. MATERIALS AND METHOD: The readiness scale of 43 items was used in four sub-titles (awareness, learning strategies, and style, motivation, team building) was developed using the Delphi method with 12 experts and was implemented for the medical students at Karamsad, Gujarat as a cross-sectional survey after a pilot trial scale from May 2021 to September 2021, using mean, the standard deviation for each item, and arrived sub-titles. The ANOVA test was used to find differences in readiness scores as per different years of the medical program. RESULT: The result demonstrates that the maximum score was obtained for the first-year medical student (149.89 ± 24.72), which dropped in year 2 (136.35 ± 32.26) but increased by the final year (147.67 ± 56.66), although not as high as the initial joining year. However, a statistically significant difference per gender was identified for a few items of the scale [(items 24 (P < 0.034), 26 (P < 0.0005), 37 (P < 0.035), and 40 (P < 0.013)]. The logistic regression analysis showed no statistical significance for the DSVS-self-directed learning readiness scale (SDLRS) score and demographic variables. CONCLUSION: The outcome of the study strongly suggests training/sensitization sessions for students to highlight the importance of a SDL approach in a digital millennium. Moreover, a longitudinal follow-up needs to be conducted for the readiness score of the students based on the developed scale and subsequent training sessions need to be organized for students as well as faculty for better outcomes for the students toward SDL sessions.